Interferon and ribavirin combination treatment synergistically inhibit HCV internal ribosome entry site mediated translation at the level of polyribosome formation. - Rajesh Panigrahi; Sidhartha Hazari; Sruti Chandra; Partha K Chandra; Sibnarayan Datta; Ramazan Kurt; Craig E Cameron; Zhuhui Huang; Haitao Zhang; Robert F Garry; Luis A Balart; Srikanta Dash (PLoS ONE, 2013)
Although chronic hepatitis C virus (HCV) infection has been treated with the combination of interferon alpha (IFN-α) and ribavirin (RBV) for over a decade, the mechanism of antiviral synergy is not well understood. We aimed to determine the synergistic antiviral mechanisms of IFN-α and RBV combination treatment using HCV cell culture.The antiviral efficacy of IFN-α, RBV alone and in combination was quantitatively measured using HCV infected and replicon cell culture. Direct antiviral activity of these two drugs at the level of HCV internal ribosome entry site (IRES) mediated translation in Huh-7 cell culture was investigated. The synergistic antiviral effect of IFN-α and RBV combination treatment was verified using both the CalcuSyn Software and MacSynergy Software.RBV combination with IFN-α efficiently inhibits HCV replication cell culture. Our results demonstrate that IFN-α, interferon lambda (IFN-λ) and RBV each inhibit the expression of HCV IRES-GFP and that they have a minimal effect on the expression of GFP in which the translation is not IRES dependent. The combination treatments of RBV along with IFN-α or IFN-λ were highly synergistic with combination indexes <1. We show that IFN-α treatment induce levels of PKR and eIF2α phosphorylation that prevented ribosome loading of the HCV IRES-GFP mRNA. Silencing of PKR expression in Huh-7 cells prevented the inhibitory effect of IFN-α on HCV IRES-GFP expression. RBV also blocked polyribosome loading of HCV-IRES mRNA through the inhibition of cellular IMPDH activity, and induced PKR and eIF2α phosphorylation. Knockdown of PKR or IMPDH prevented RBV induced HCV IRES-GFP translation.We demonstrated both IFN-α and RBV inhibit HCV IRES through prevention of polyribosome formation. The combination of IFN-α and RBV treatment synergistically inhibits HCV IRES translation via using two different mechanisms involving PKR activation and depletion of intracellular guanosine pool through inhibition of IMPDH.